Framed - Keene, Carolyn (New York : Aladdin Paperbacks, 2006)
Nancy Drew tries to free a prince who has been framed for the theft of a painting.
"Nancy Drew 75th anniversary."
008-012.
Accelerated Reader AR
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Princes -- Fiction; Art thefts -- Investigation -- Fiction; Mystery and detective stories; Mystery fiction